PERLINDUNGAN HUKUM TERHADAP HAK WARGA NEGARA DALAM MEMPEROLEH PENDIDIKAN - Masurip Masurip (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2022)
The School Operational Assistance Fund (BOS) has an important contribution to increasing access to education in Indonesia. This is marked by a decrease in the number of children dropping out of school and an increase in the number of children returning to school. Article 31 paragraph (1) and (2) of the 1945 Constitution states that every citizen has the right to education and every citizen is obliged to attend basic education and the government is obliged to finance it. This study aims to determine and analyze legal protection for citizens in the field of education. The normative juridical research method with the statutory approach to the analysis technique model used is the Miller and Huberman analysis model.